Are trainees lifting heavy enough? self-selected loads in resistance exercise: a scoping review and exploratory meta-analysis - Steele, J.; Malleron, T.; Har-Nir, I.; Androulakis-Korakakis, P.; Wolf, M.; Fisher, J. P.; Halperin, I. (Sports Medicine, 2022)
Background: Traditionally, the loads in resistance training are prescribed as a percentage of the heaviest load that can be successfully lifted once (i.e., 1 Repetition Maximum [1RM]). An alternative approach is to allow trainees to self-select the training loads. The latter approach has benefits, such as allowing trainees to exercise according to their preferences and negating the need for periodic 1RM tests. However, in order to better understand the utility of the self-selected load prescription approach, there is a need to examine what loads trainees select when given the option to do so. Objective: Examine what loads trainees self-select in resistance training sessions as a percentage of their 1RM. Design: Scoping review and exploratory meta-analysis. Search and Inclusion: We conducted a systematic literature search with PubMed, Web of Science, and Google Scholar in September 2021. We included studies that (1) were published in English in a peer-reviewed journal or as a MSc or Ph.D. thesis; (2) had healthy trainees complete at least one resistance-training session, composed of at least one set of one exercise in which they selected the loads; (3) trainees completed a 1RM test for the exercises that they selected the loads for. Eighteen studies were included in our main meta-analysis model with 368 participants. Results: Our main model indicated that on average participants select loads equal to 53% of their 1RM (95% credible interval [CI] 49-58%). There was little moderating effect of training experience, age, sex, timing of the 1RM test (before or after the selected load RT session), number of sets, number of repetitions, and lower versus upper body exercises. Participants did tend to select heavier loads when prescribed lower repetitions, and vice versa (logit(yi) = - 0.09 [95% CI - 0.16 to - 0.03]). Note that in most of the analyzed studies, participants received vague instructions regarding how to select the loads, and only completed a single session with the self-selected loads. Conclusions: Participants selected loads equal to an average of 53% of 1RM across exercises. Lifting such a load coupled with a low-medium number of repetitions (e.g., 5-15) can sufficiently stimulate hypertrophy and increase maximal strength for novices but may not apply for more advanced trainees. Lifting such a load coupled with a higher number of repetitions and approaching or reaching task failure can be sufficient for muscle hypertrophy, but less so for maximal strength development, regardless of trainees' experience. The self-selected load prescription approach may bypass certain limitations of the traditional approach, but requires thought and further research regarding how, for what purposes, and with which populations it should be implemented.